2022
DOI: 10.1186/s12870-022-03585-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and transcriptome profiling unveil the mechanisms of light-induced anthocyanin synthesis in rabbiteye blueberry (vaccinium ashei: Reade)

Abstract: Background Blueberry is one of the most important fruit crops worldwide. Anthocyanin is an important secondary metabolites that affects the appearance and nutritive quality of blueberries. However, few studies have focused on the molecular mechanism underlying anthocyanin accumulation induced by light intensity in blueberries. Results The metabolic analysis revealed that there were 134 significantly changed metabolites in the natural light compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…We identified 533 metabolites during the development of the R. roxburghii “Rr-5” fruit, which was fewer than the metabolites in the six different R. roxburghii genotypes identified by Jiang et al [ 6 ], indicating that different genotypes of R. roxburghii exhibited significant differences in metabolites. Guo et al detected 134 metabolites grouped into 11 classes in blueberry [ 32 ]. Chen et al identified 407 metabolites in strawberry [ 33 ], while 352 metabolites were detected and identified in citrus [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified 533 metabolites during the development of the R. roxburghii “Rr-5” fruit, which was fewer than the metabolites in the six different R. roxburghii genotypes identified by Jiang et al [ 6 ], indicating that different genotypes of R. roxburghii exhibited significant differences in metabolites. Guo et al detected 134 metabolites grouped into 11 classes in blueberry [ 32 ]. Chen et al identified 407 metabolites in strawberry [ 33 ], while 352 metabolites were detected and identified in citrus [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…F3’5’H is a class of cytochrome P450-dependent flavonoid hydroxylases that function in the hydroxylation of dihydroflavonol at the 3’ and 5’ positions of the B-ring. Previous studies ( Guo et al., 2022 ) have shown that the VcF3’5’H4 gene may play an important role in the light-induced blueberry anthocyanin synthesis pathway. Two UFGT genes that are involved in the conversion of anthocyanidins to anthocyanins were highly expressed in blue fruit but not in green fruit and were cis -targeted by lncRNAs with the same expression patten.…”
Section: Discussionmentioning
confidence: 98%
“…Light is one of the most important factors involved in ACN biosynthesis, and light intensity, light quality, and photoperiod determine the concentration of ACNs. In addition, the activity of enzymes and genes related to ACN synthesis increases when crops are continuously exposed to radiation [51]. Therefore, the activity of the ACN synthetase enzyme increases under long photoperiods, which increases the ACN content.…”
Section: Discussionmentioning
confidence: 99%